Standardization of foliar application of molybdenum for high yield of cauliflower (Brassica oleracea convar botrytis var botrytis) on Alfisol of Bihar plateau - Kotur, Shivaputra C (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1986-92 on ’Pusa Snowball 1 ’ cauliflower [Brassica oleracea L. convar botrytis (L.) Alef. Var botrytis L.) grown on a molybdenum-deficient soil to standardize the foliar application of Mo to ameliorate whiptail malady and achieve high curd yield. A significant improvement in the leaf breadth (12.0-13.3 cm), curd diameter (16.8-18.8 cm). weight(710-804 g) as well as Mo content of leaf (0.70-11.48 Âµg/g) was observed when ammonium molybdate was applied as foliar spray. The increase in concentration (0.05-0.2%) and number of sprays increased the Mo content of leaf but the effect of the former was significant. Application of ammonium molybdate at 0.1 % resulted in 6.87 Âµg/g Mo content of leaf and curd yield of 24.8 tonnes/ha. Three sprays of 0.1% ammonium molybdate with the addition of either surfactant (0.1 % wetting agent) or humectant (0.2% calcium chloride) greatly increased the Mo content of leaf (11.68-12.79 Âµg/g) and reduced the curd diameter (16.4-17.0 cm). weight (688-703 g) and yield (17.72-17.74 tonnes/ha) compared with 4 sprays of 0.1 % ammonium molybdate without additives (7.98 Âµ/g Mo, 17.8 cm, 783 g and 29.73 tonnes/ha respectively). Three sprays of 0.0125% ammonium molybdate with surfactant or humectant was as effective as 0.1 % molybdate without additives in increasing the curd yield and net returns as well as in reducing the leafy or ricey (unmarketable) curds caused by Mo deficiency. A quadratic relationship was observed between curd yield and Mo content of leaf, and on that basis the maximum curd yield occurred at 6.73 Âµg/g Mo in the leaf.